Assessment of Water Quality Based on Land Use in an Upper Watershed Using the STORET Method - Istika Nita; Anggraini Aurina Putri; Rony Irawanto (The University of Lampung, 2025)
Land use change significantly affects water quality, particularly in watersheds. This study assessed the water quality of the Upper Welang Watershed, East Java, using the STORET method in relation to land use types. Water quality assessment involves comparing measured data with the National Water Quality Standard (Government Regulation No. 22 of 2021). Water samples were collected during the dry season (March to July 2023) from forest, plantation, rice field, dry field, settlement, and industrial areas. Parameters analyzed included pH, DO, BOD, COD, NO3, TDS, Pb, Cd, and coliforms. Results showed that water quality declined in areas with high anthropogenic activity, particularly in industrial and settlement zones, with COD and NO3 levels exceeding national standards. Rivers with stable substrates and sufficient habitats exhibit better water quality. The findings highlight the importance of land use management in watershed conservation